Motivations and Meanings of Environmental Volunteer Experiences at Eco-Leisure Destinations in New Zealand - Fukushima, Nobuyuki (Auckland University of Technology, 2016)
Environmental volunteering is becoming more vital and fundamental for the health of community and environment. The purpose of this study is to identify characteristics of environmental volunteers and gain an understanding of the totality of their experiences from multidisciplinary perspectives. A theoretical model was proposed based on the Volunteer Process Model (VPM) which includes relationships between motivations of volunteers, leisure involvement in volunteering, and place attachment to ecoleisure/tourism destinations. This study adopted positivist perspectives, and was conducted through surveys for volunteers at eco-leisure/tourism destinations in the Hauraki Gulf in New Zealand. A total of 396 valid responses were collected and analysed. Results from the sample revealed that some specific socio-demographics were related to participation in environmental volunteering at eco-leisure/tourism settings, such as age, gender, the frequency of volunteering (episodic/ongoing), and the origin of participants (domestic/international). The analysis of socio-demographics identified three dominant groups of environmental volunteers, namely leisure volunteers, ongoing volunteers, and tourist volunteers. An exploratory factor analysis (EFA) for motivation items identified six factors of motivation; values of nature, career, enhancement, protective, social, and leisure. The importance of these factors differed between episodic and ongoing volunteers, as well as between domestic and international volunteers. While ongoing volunteers put importance on values of nature and leisure motives, episodic volunteers were more motivated by enhancement and protective factors. A confirmatory factor analysis (CFA) on leisure involvement scales identified three dimensions as previous research; attraction, centrality, and self-expression. Also the CFA for place attachment scales revealed two dimensions; place identity and place dependence. The importance of these dimensions for environmental volunteers also differed by volunteer attributes. The proposed model showed good fit indices, in which the motivation factors predicted the importance of leisure involvement dimensions, and leisure involvement dimensions affected the strength of place attachment to the volunteering sites. In addition, the results of the structural equation model (SEM) identified that values of nature and social factors had the most positive effect on leisure involvement overall, while leisure and enhancement were relatively important factors for leisure involvement only in the episodic volunteer group. Episodic volunteers were more driven by endogenous motivations, while ongoing volunteers were more driven by exogenous motivations. In addition, the involvement dimension of self-expression had a significant effect on the place attachment felt by ongoing volunteers, while centrality had a more significant effect on the sense of place attachment of episodic volunteers. This study identified three segments of environmental volunteers, with differences in motivations, leisure involvement, and place attachment seen between episodic and ongoing volunteers, as well as between domestic and international volunteers. In addition, this study demonstrated the validity of a new volunteer process model for environmental volunteers including for both episodic and ongoing volunteers. The results of the survey offer new perspectives of leisure environmental volunteering and identify the various volunteer experiences of domestic and international volunteers who choose spend their leisure time in restoration activities. The findings and implications can contribute to a number of organisations in societies, including governmental and non-governmental organisations, non-profit organisations, and tourism operators.
Keywords: Volunteerism; Volunteer tourism; Leisure; Motivation; Leisure Involvement; Place Attachment; Volunteer Process Model